Pemberitaan Bangkitnya Pki dalam Media Massa (Analisis Semiotika Sosial M.A.K Halliday pada Isu Pemberitaan Bangkitnya Partai Komunis Indonesia di Media Online) - Ade Tuti Turistiati (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Mass media coverage on the rise of the Communist Party of Indonesia (PKI) became public attention including its news on online media. Online media that reported it among others are Republika.co.id, Liputan6.com, and Merdeka.com. The purpose of this study is to find out how online media in Indonesia discourse news text in the issue of the rise of PKI by using a qualitative approach, social semiotics method version of M.A.K Halliday. As an online medium that has certain characteristics such as speed, it was clearly seen in this news. The media became biased and ignored journalistic principles, including the principle of online journalism. The three online media that became the object of this study showed images and illustrations which were provocative and not in accordance to the reported facts. The three media have done news construction subjectively and were less professional.